2022
DOI: 10.1093/infdis/jiac451
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of an Additional mRNA-1273 SARS-CoV-2 Vaccination in People With HIV With Hyporesponse After Primary Vaccination

Abstract: Background The COVIH-study is a prospective SARS-CoV-2 vaccination study in 1154 people with HIV (PWH), of whom 14% showed a reduced or absent antibody response after primary vaccination. We evaluated whether an additional vaccination boosts immune responses in these hyporesponders. Methods Consenting hyporesponders received an additional 100µg mRNA-1273 vaccination. The primary endpoint was the increase in antibodies 28 days… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…The findings suggested that PLWH may need an additional booster dose on top of the two doses. In face of continuous epidemics, an additional dose of COVID-19 vaccine was proved to be effective and induced significant higher antibody levels compared with the second dose (32)(33)(34). Since PLWH have an increased risk of breakthrough infections compared to the general population, a booster dose to PLWH would be an alternative method to sustain sufficient protection.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggested that PLWH may need an additional booster dose on top of the two doses. In face of continuous epidemics, an additional dose of COVID-19 vaccine was proved to be effective and induced significant higher antibody levels compared with the second dose (32)(33)(34). Since PLWH have an increased risk of breakthrough infections compared to the general population, a booster dose to PLWH would be an alternative method to sustain sufficient protection.…”
Section: Discussionmentioning
confidence: 99%
“…The initial search produced 772 articles, of which 323 were duplicate publications. Eight of the 449 remaining articles included studies involving measurements on the humoral immunity against SARS-CoV-2 in PLWH after a third dose of an mRNA-based COVID-19 vaccine and were eligible for inclusion in this study (9)(10)(11)(12)(13)(14)(15)(16). Five of the studies also investigated the cellular immunity (11,(13)(14)(15)(16).…”
Section: Resultsmentioning
confidence: 99%
“…Eight of the 449 remaining articles included studies involving measurements on the humoral immunity against SARS-CoV-2 in PLWH after a third dose of an mRNA-based COVID-19 vaccine and were eligible for inclusion in this study (9)(10)(11)(12)(13)(14)(15)(16). Five of the studies also investigated the cellular immunity (11,(13)(14)(15)(16). Out of the eight included studies, five were case-control studies (10)(11)(12)(13)(14) and three were case studies (9,15,16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although SARS-CoV-2 specific IFN-gamma production increased after the third dose, it remained significantly lower among SARS-CoV-2 naive PWH compared with HIV(À) controls [15]. In a Dutch cohort of PWH with a hypo-response after a primary vaccination regimen, an additional dose of mRNA-1273 induced a robust serological response in 64 of 66 PWH after 1 month, including neutralizing antibodies to wild-type virus, as well as T-cell responses, regardless of the primary vaccination regimen or patient characteristics [16]. A German study found that, after the second and the third vaccination, the titers of neutralizing antibodies against wild-type SARS-CoV-2 were slightly reduced in PWH compared with controls, but the reduction against Delta and Omicron variants was more pronounced.…”
Section: How Effective Are Covid-19 Vaccines In Inducing Immune Respo...mentioning
confidence: 88%